Contextual Effect of the Integrated Non-Communicable Disease Health Post on the Performance of Community Health Workers: A Multilevel Analysis Evidence from Karanganyar, Central Java - Eka Siti Chasanah; Endang Sutisna Sulaeman; Setyo Sri Rahardjo (Masters Program in Public Health, Sebelas Maret University, 2020)
Background: Epidemiological transition is causing a shift from Communicable to NonCommunicable Diseases (NCD). NCD is a serious threat because it impacts decreasing productivity and increasing economic and social burdens for the community. The control of NCD risk factors in Indonesia is carried out by empowering the community through the Integrated Non-Communicable Diseases Health Post (Posbindu NCD). One of the important factors determining the success of implementing Posbindu is the role of cadres. This study aims to analyze the factors that affect the performance of Posbindu cadres.Subjects and Method: This was an analytic observational study with a cross-sectional design. The study was conducted in 25 posbindus in Karanganyar, Central Java, from February to April 2020. A sample of 200 cadres from 25 cadres was selected by stratified random sampling. The dependent variable was the performance of the Posbindu cadres. The independent variables were training, ability, length of employment, motivation, the leadership of the Posbindu chairman, social network support and appreciation. Data were analyzed using multilevel logistic regression with Stata 13.Results: Job performance increased with training (b= 1.75; 95% CI= 0.28 to 3.22; p= 0.019), good ability (b= 2.50; 95% CI= 0.95 to 4.04; p= 0.002), tenure ≥1 year (b= 1.99; 95% CI= 0.05 to 3.92; p= 0.044), strong motivation (b= 2.57; 95% CI= 1.25 to 3.89; p <0.001), good leadership of Posbindu chairman (b= 1.73; 95% CI= 0.44 to 3.03; p= 0.009), and strong social network support (b= 1.24; 95% CI= 0.14 to 2.34; p= 0.028). Incentive increased job performance, but it was statistically non-significant (b= 1.19; 95% CI= -0.35 to 2.73; p= 0.132). Posbindu had a strong contextual effect on job performance with an ICC of 62.73%.Conclusion: Job performance increases with training, good abilities, tenure ≥1 year, strong motivation, good leadership of Posbindu chairman, strong social network support, and appropriate incentives. Posbindu has a strong contextual effect on job performance.Keywords: performance, cadre, non-communicable diseaseCorrespondence: Eka Siti Chasanah. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: ekasc12@gmail.com. Mobile: +6281329017587.Journal of Health Policy and Management (2020), 05(03): 204-214https://doi.org/10.26911/thejhpm.2020.05.03.06